3‐Methyl‐4‐oxa‐5‐azahomoadamantane as an Organocatalyst for the Aerobic Oxidation of Primary Amines to Oximes in Water. Issue 6 (16th March 2015) - Yu, Jiatao; Jin, Yong; Lu, Ming
Abstract A simple and efficient catalytic system for the aerobic oxidation of primary amines into corresponding oximes has been developed, with 3‐methyl‐4‐oxa‐5‐azahomoadamantane as catalyst, acetaldoxime as co‐catalyst and water as solvent. This process, which uses oxygen (O2) as an economic and green oxidant and water as a green solvent, tolerates a wide range of substrates, affording the target oximes in moderate to excellent yields. It was found that high selectivity was achieved when 3‐methyl‐4‐oxa‐5‐azahomoadamantane was used, and E‐type oximes were the only detected products. A possible mechanism for this catalytic process is proposed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>